2022
DOI: 10.1038/s41467-022-32665-7
|View full text |Cite
|
Sign up to set email alerts
|

Omicron SARS-CoV-2 mutations stabilize spike up-RBD conformation and lead to a non-RBM-binding monoclonal antibody escape

Abstract: Omicron SARS-CoV-2 is rapidly spreading worldwide. To delineate the impact of emerging mutations on spike’s properties, we performed systematic structural analyses on apo Omicron spike and its complexes with human ACE2 or S309 neutralizing antibody (NAb) by cryo-EM. The Omicron spike preferentially adopts the one-RBD-up conformation both before and after ACE2 binding, which is in sharp contrast to the orchestrated conformational changes to create more up-RBDs upon ACE2 binding as observed in the prototype and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 72 publications
5
69
0
Order By: Relevance
“…This correlates with our high-speed AFM observations, showing less pronounced RBD opening and reduced angular and lateral RBD displacements, and is also consistent with recent EM studies reporting steric restrictions arising from a binding interface between two adjacent RBDs 51 , 52 , 55 , 56 that may lead to tight packing of the Omicron (B.1.1.529) RBDs 57 in the 3 RBD-down states and a slower transition of the Omicron (B.1.1.529) Spike from one-RBD-up to two-RBD-up or three-RBD-up conformations 51 . Furthermore, our data is also in line with a previous study demonstrating that a one-up RBD conformation of the Omicron (B.1.1.529) Spike is preserved after ACE2 binding, which is in stark contrast to other VOCs, where ACE2 binding of one RBD triggers the exposure of further up-RBDs 58 .…”
Section: Discussionsupporting
confidence: 93%
“…This correlates with our high-speed AFM observations, showing less pronounced RBD opening and reduced angular and lateral RBD displacements, and is also consistent with recent EM studies reporting steric restrictions arising from a binding interface between two adjacent RBDs 51 , 52 , 55 , 56 that may lead to tight packing of the Omicron (B.1.1.529) RBDs 57 in the 3 RBD-down states and a slower transition of the Omicron (B.1.1.529) Spike from one-RBD-up to two-RBD-up or three-RBD-up conformations 51 . Furthermore, our data is also in line with a previous study demonstrating that a one-up RBD conformation of the Omicron (B.1.1.529) Spike is preserved after ACE2 binding, which is in stark contrast to other VOCs, where ACE2 binding of one RBD triggers the exposure of further up-RBDs 58 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, from our alignments, we observed that the selected mutations remain consistent in all the subsequently emerged variants to date. Previous studies informed a stronger binding between Omicron Spike protein and ACE2 (23,56,72) and a reduction of binding between Omicron Spike protein and Abs (52,58,70). The predictive increased binding affinity caused by N501Y was consistent with these findings, while the other calculations may slightly differ.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies using cryo-EM structures and constant-pH Monte Carlo simulations showed that enhanced virulence could also be a consequence of an improved viral stability of the trimeric Spike in the open state with the better RBD availability to ACE2, rather than only through the alteration in the RBD-ACE2 interaction itself (10,67,68). Meanwhile, more research revealed that the Spike protein of Omicron is more likely to have one RBD-up conformation, not only maintaining the interaction with ACE2 but also restricting the recognition of antibody (69,70). In our in-silico work, we identified that three N to K mutations reported in Omicron and its subvariants may contribute to a mild preference of all the RBD-down conformation, compared to the prototype Spike protein.…”
Section: Discussionmentioning
confidence: 99%
“…The Spike interacts with its ACE2 receptor in its “up” conformation [ 46 ]. However, the Spike trimer of Omicron BA.1 and subvariant BA.2 was reported to assume more the RBD “down” conformation that is stabilised by a strong network of inter-protomer contacts leading to its higher thermostability [ 47 , 48 ]. Therefore, we studied the sensitivity of the Spike subvariants to conformational changes in response to ACE2.…”
Section: Resultsmentioning
confidence: 99%